Advances on Nanomedicines for Diagnosis and Theranostics of Hepatic Fibrosis. Issue 7 (3rd May 2021) - Dai, Xinghang; Zeng, Yujun; Zhang, Hu; Gu, Zhongwei; Gong, Qiyong; Luo, Kui
Abstract : Hepatic fibrosis is induced by chronic hepatic injuries before it turns into hepatic cirrhosis/carcinoma. It is characterized by the formation of collagen and other extracellular matrices around damaged hepatic tissues; consequently, the normal architecture of liver would be disrupted and its function impaired. Diagnosis of hepatic fibrosis, especially at the early stage, is crucial because most fibrotic changes are reversible during the hepatic fibrosis stage. However, early and more accurate diagnosis of hepatic fibrosis still remains a great challenge. With their promising structural adjustability and targeting ability, nanomedicines have recently been introduced to improve diagnosis of hepatic fibrosis. By targeting fibrogenic cells, receptors, and extracellular matrix components, these nanomedicines can achieve detection of hepatic tissues with high sensitivity and specificity at the early stage. The use of nanomedicines can also enable theranostics of this chronic hepatic disease. This review aims to present an overview of recent advances of nanomedicines in diagnosis and theranostics of hepatic fibrosis. Abstract : The use of nanomedicines enables the diagnosis of hepatic fibrosis with high sensitivity, high specificity at the early stage by targeting fibrogenic cells, receptors, and extracellular matrix components. Theranostics can also be promoted by incorporating fibrosis‐targeting diagnostic and therapeutic agents into one nanomedicine. Herein, the recent advances of nanomedicine for diagnosis of hepatic fibrosis are discussed.